Pelatihan Desain Packaging Parfum Body Menggunakan Kertas Daur Ulang Kepada Siswa SMK Bina Insan Mandiri Srengseng - Suhada, Resa Taruna; Riadi, Selamet (Jurnal Pengabdian Kepada Masyarakat Patikala, 2026)
The use of perfume has now become a lifestyle. Besides providing fragrance and freshness to the wearer, it can also boost self-confidence by eliminating body odor. Perfume is used by people of all ages, from babies and children to teenagers and adults. The perfume market in Indonesia experiences annual growth. Perfume, or fragrance oil, is a mixture of essential oils and aroma compounds, fixatives, and solvents used to impart a pleasant scent to the human body, objects, or rooms. The amount and type of solvent mixed with the fragrance oil determine whether a perfume is considered a perfume extract, Eau de parfum, Eau de toilette, or Eau de Cologne (wikipedia). Local perfumes only became popular in Indonesia between 2017 and 2018. The Central Statistics Agency (BPS) recorded that there were 129,137 medium and large trading businesses in Indonesia in 2020. Of that number, the majority, or approximately 39% of business owners, were high school graduates. The method used included theoretical explanations, perfume-making demonstrations, and a practical session, where each participant created a 10 ml bottle of perfume. The training was attended by the Foundation's management, the principal, and students. A total of 76 students participated in the training. Participants were divided into several groups. All students successfully created perfume. Participants gained knowledge and skills in perfume-making as an alternative to perfume entrepreneurship.